2022
DOI: 10.3390/molecules27175462
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant Effect of Crocin in Mice with Chronic Mild Stress

Abstract: This study aimed to investigate the antidepressant property of crocin (Crocetin digentiobiose ester) using a chronic mild stress (CMS)-induced depression model in experimental mice. The tail suspension test (TST) and the sucrose preference test were used to evaluate the antidepressant effect on albino mice of either sex after three weeks of CMS. The period of immobility in the TST and percentage preference for sucrose solution were recorded. By monitoring brain malondialdehyde (MDA) level, catalase (CAT) activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…Alsanie et al found that the therapeutic effect of C. sativus extract on mild and moderate depressive disorder is comparable to antidepressants, such as imipramine and fluoxetine [ 10 , 60 61 ]. The antidepressant activity of C. sativus extract was exerted by regulating the serotonin, norepinephrine, and dopamine levels in the brain [ 62 64 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Alsanie et al found that the therapeutic effect of C. sativus extract on mild and moderate depressive disorder is comparable to antidepressants, such as imipramine and fluoxetine [ 10 , 60 61 ]. The antidepressant activity of C. sativus extract was exerted by regulating the serotonin, norepinephrine, and dopamine levels in the brain [ 62 64 ].…”
Section: Reviewmentioning
confidence: 99%
“…Crocins are utilized extensively as colorants and flavoring agents in the food, cosmetics, and pharmaceutical industries [ 5 ]. They exhibit a broad spectrum of pharmacological activity, including antitumor [ 6 ], anti-inflammatory [ 7 ], hepatoprotective [ 8 ], nephroprotective [ 9 ], antidepressant [ 10 ], antioxidant [ 11 ], and antidiabetic [ 12 ] properties. The Saffron Multi-glycoside Tablet (Xihonghua Zonggan Pian) ameliorates myocardial ischemia or myocardial infarction induced by coronary ligation.…”
Section: Introductionmentioning
confidence: 99%
“…The remaining substances needed for this research came from reputable vendors, and the labels were saved for later reference. The doses of apigenin [16] and imipramine [36] were selected based on our earlier findings.…”
Section: Chemicals and Reagentsmentioning
confidence: 99%
“…All treatments were given orally for three weeks before subjecting the animals to their respective stress pattern of CMS. A sucrose preference test was conducted on day 21 at 60 min following CMS [36].…”
Section: Experimental Groupingmentioning
confidence: 99%
See 1 more Smart Citation